The Paratuberculosis Paradigm Examined: A Review of Host Genetic Resistance and Innate Immune Fitness in Mycobacterium avium subsp. Paratuberculosis Infection - Kravitz, Amanda; Pelzer, Kevin; Sriranganathan, Nammalwar (Frontiers in Veterinary Science, 2021)
Paratuberculosis, or Johne's Disease (JD) is a debilitating chronic enteritis mainly affecting ruminants caused by Mycobacterium avium subsp. paratuberculosis (MAP). This organism causes worldwide economic losses to the livestock industry, and is of public health importance due to the potential zoonotic risk between MAP and Crohn's disease (CD) in humans. Without economical treatments, or a vaccine capable of preventing infection without causing cross-reactions with bovine tuberculosis, test-and-cull methods for disease control are imperative. Unfortunately, difficulties in diagnostics and long subclinical stage hinder adequate control and is further complicated by variation in MAP exposure outcome. Interestingly, the majority of infections result in asymptomatic presentation and never progress to clinical disease. One contributing factor is host genetics, where polymorphisms in innate immune genes have been found to influence resistance and susceptibility to disease. Candidate genes identified across studies overlap with those found in CD and tuberculosis including; Solute carrier family 11 member 1 gene (SLC11A1), Nucleotide-binding-oligomerization domain containing gene 2 (NOD2), Major histocompatibility complex type II (MHC-II), and Toll-like receptor (TLR) genes. This review will highlight evidence supporting the vital role of these genes in MAP infection outcome, associated challenges, and implications for the future of JD research.